The Analysis of Strength Properties by Using Stone Dust and Recycled Crushed Concrete (International Journal of Innovative Research in Engineering & Management, 2023)
Concrete is one of the most widely used  materials worldwide. In 2009, the International Energy  Agency reported that approximately 25 Gt of concrete is  used worldwide each year, equivalent to more than 3.8  tonnes of concrete per person per year. Total construction  demand is expected to reach 48.3 billion tonnes by 2015.  The highest consumption was in Asia and the Pacific.  Demolition to build new buildings generates a lot of waste.  Among the various construction and demolition wastes,  concrete waste accounts for 50% of the total waste  generation. The top five causes of large amounts of  concrete waste are overordering, shipping damage,  installation loss, poor technology and design changes. The  most common way to dispose of this waste is to dump it in  a landfill, which can pollute air and water because of its  high alkalinity. Therefore, recycled aggregate concrete  (RAC) is an alternative to using natural aggregate (NA) in  concrete. Recycled Concrete Aggregate (RCA) is  aggregate obtained by recycling clean concrete waste and  demolished structures. The effect of different proportions  of crushed stone dust and recycled concrete on the  compressive strength of M30 concrete was studied. The  effect of different ratios of crushed stone dust and ground  recycle concrete on the flexural and tear strength of M30  concrete is also observed.
Keywords: Secondary Crushed Stone; Stone Dust; Coarse Aggregate; Fine Aggregate; Cement; Water